CONSORT statement: extension to cluster randomised trials (BMJ Publishing Group, 2004)
Reports of cluster randomised trials require additional information to allow readers to interpret them accurately The effective reporting of randomised controlled trials has received useful attention in recent years. Many journals now require that reports conform to the guidelines in the Consolidated Standards of Reporting Trials (CONSORT) statement, first published in 19961 and revised in 2001.2 The statement includes a checklist of items that should be included in the trial report. These items are evidence based whenever possible and are regularly reviewed.3 The statement also recommends including a flow diagram to show the flow of participants from group assignment through to the final analysis.